Analisis Aktivitas Belajar Siswa melalui Media Pembelajaran Monopoli RAGANUSA pada Mata Pelajaran IPAS di Kelas V SD - Aulia Rahmadanti, Daffa; Putri Sintiyawati, Ersha; Ardelia Qatrunada, Talitha; Wijayanti, Kurnia; Dwi Aryanti, Ratna; Masfuah, Siti (Jurnal Ilmiah Telaah, 2025)
Low learning activity is still a challenge in learning Natural and Social Sciences (IPAS) in elementary schools, especially on the material of Indonesian cultural diversity. This study aims to analyze the effectiveness of using RAGANUSA monopoly learning media in increasing the learning activities of fifth grade students in IPAS subjects. Monopoly RAGANUSA is a learning media based on a modified monopoly game with the content of the archipelago's cultural diversity to create contextual, fun, and meaningful learning. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The research subjects consisted of teachers and 10 fifth grade students of SD 4 Dersalam. Data analysis used the Miles and Huberman model which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the RAGANUSA Monopoly media was able to significantly increase students' learning activities, especially in the aspects of interest, active involvement, and positive attitudes towards learning. Validation by material experts, media, and practitioners stated that this media is very feasible to use, both from the aspects of content, concept clarity, visual design, technical, and innovation. The response of teachers and students to the use of the media was also very positive; students showed high enthusiasm, while teachers felt helped in delivering the material in a more interesting and interactive manner.